Practice patterns and outcomes following radiation dose de‐escalation for oropharyngeal cancer. (23rd May 2019) - White, Richard; Abel, Stephen; Hasan, Shaakir; Verma, Vivek; Greenberg, Larisa; Colonias, Athanasios; Wegner, Rodney E.
Abstract : Objectives/Hypothesis: Numerous trials are evaluating radiotherapy (RT) de‐escalation for human papillomavirus (HPV)‐mediated (HPV+) oropharyngeal squamous cell carcinoma (OPSCC). Herein, we evaluated the degree to which de‐escalated RT is delivered in the United States, as well as comparative outcomes with full‐dose RT as stratified for HPV status. Study Design: Retrospective database review. Methods: We identified patients diagnosed with OPSCC in the National Cancer Database, excluding those with stage I/II disease, unknown HPV status, receiving surgery or not receiving external beam radiation therapy to the primary site, receipt of radiation doses >75 or <54 Gy, radiation treatment course duration <25 or >75 days, and unknown or inadequate (<2 months) follow‐up. Multivariable logistic regression analysis identified variables associated with delivery of de‐escalated RT (<66 Gy). Overall survival of HPV+ and non–HPV‐mediated (HPV−) disease was compared between full‐dose and de‐escalated approaches. Results: Altogether, 617 and 551 patients were HPV+ and HPV−, respectively. De‐escalated RT was delivered in 16.9% HPV+ and 15.2% of HPV− disease, respectively. Older patients and omission of systemic therapy were more likely to receive de‐escalated RT. In HPV+ patients, 3‐ and 5‐year survival rates were 83% and 80% in the de‐escalated cohort versus 83% and 78% in the full‐dose group ( P = .83). In HPV− patients, corresponding 3‐ and 5‐year survival rates were 29% and 23% versus 61% and 51% ( P = .001). Conclusions: National utilization of de‐escalated RT for OPSCC is low (15%–20%), but does not seem to impact overall survival in HPV+ (but not HPV−) patients. The caveats of this heterogeneous, retrospective analysis require corroboration from a number of ongoing randomized trials. Level of Evidence: 2c Laryngoscope, 130:E171–E176, 2020